Current concept on pediatric low-grade glioma in the era of molecular diagnosis - Tzu-Chiang Peng; Ching-Ying Wang; Yi-Yen Lee (Tungs’ Medical Journal)
Central nervous system tumors are the most common solid tumors and the second leading cause of cancer-related deaths among pediatric patients. Despite recent advances in surgical technique, chemotherapy, and radiotherapy, it disappointedly relates to significantly profound morbidity compared to other cancers. The current therapeutic strategy leads to a high incidence of adverse effects. Pediatric brain tumor survivors have a higher risk of neurocognitive decline and endocrine, neurological, and social domain impairment than the age-matched group. A recent study has made a meaningful progress in the field of genetics and shed light on the broad molecular heterogeneity of pediatric brain tumors. This insight has impacted the current clinical practice and opened an avenue to potential therapeutic choice. Here, we reviewed the progress in the understanding of pediatric low-grade glioma and emerging target therapy.